The Covid-19 sanitary crisis and the productivity and technological vulnerability of the Health Economic-Industrial Complex in Brazil within the context of financialization - Sarti, Fernando; Hiratuka, Celio; Fonseca, Camila Veneo Campos (Cadernos do Desenvolvimento, 2023)
The paper analyses strategy changes in global leader firms of HEIC in order to evaluate the new accumulation dynamics and point out, in a preliminary way, the implications for the overcoming of the economic and social challenges in the health sector in Brazil. The hypothesis is that both the demand and the vulnerability of SUS, though having been accentuated in the sanitary crisis, had already been present due to the structural changes im- posed on HEIC with the event of this significant set of shifts in the strategies of capitalist accumulation. Understanding these changes on a global scale is crucial to evaluate the structural productive and technological vulnerability of HEIC in Brazil and to design feasible, effective public policies to consolidate SUS in connection with productive and technological advances, thus promoting long- term socioeconomic development.